Development of a 3-D Dynamic Fracture Process Analysis code to Simulate Intermediate Loading Rate. Issue 4 (October 2021) - Fukuda, D.; Cho, S.H.; Min, G.J.; Liu, H.Y.; Kodama, K.; Fujii, F.
Abstract: For the stimulation solutions for oil and gas wells, the creation of multiple fractures that extend deep into surrounding rock formation is important to improve productivity or injectivity. For this purpose, the application of "not too slow but not too fast dynamic loading rate (hereafter intermediate dynamic loading rate)" has been proposed in the literature, which utilizes solid propellants. While previous researchers have experimentally demonstrated their applicability, our understanding of the detailed mechanism of rock fracturing for such an intermediate dynamic loading rate has not been mature enough. We have self-developed a state-of-the-art 3D combined finite-discrete element simulator that can model the complex dynamic fracture process of rocks. This paper applied the developed code to investigate its applicability to this class of problem characterized by the intermediate dynamic loading rate. NRC (new rock cracker) based on the water vaporized pressure due to the thermit reaction of the non-explosive ingredients was used. Based on the measured pressure as an input to the developed code, the 3D dynamic fracture process analysis (DFPA) was conducted. The involving dynamic fracture process and resultant fracture pattern were discussed. In addition, the required future tasks for more reasonable numerical simulation were also pointed out.